KOMUNIKASI ANTARBUDAYA STUDI NEGOSIASI WAJAH DALAM INTERAKSI ETNIK BATAK DAN ETNIK MINANG DI DURI KELURAHAN GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS - Maduma Yanti Sari; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Indonesian society is a plural society. This pluralism is made up of diverse national backgrounds in tribes, religions, races and classes. In addition to this every culture also has certain characteristics such as differences in language, customs, and habits, food and norms and values are believed. This makes the two ethnics in the city Duri ethnic Batak and ethnic Minang require to be able to adapt to different cultures. In the process of daily interaction the differences between ethnic Batak and ethnic Minang cause misunderstandings occur in everyday interactions seen from the form Facework seen from the negotiation of the face of each ethnic. This study aims to determine the forms of intercultural communication facework between ethnic batak and ethnic Minang when interacting in their daily life as well as ethnic conflict management in facial rescue to maintain their respective cultural identity in the city of Duri Kelurahan Gajah Sakti, Mandau District Bengkalis District.This research uses qualitative method with Phenomenology approach by Alfred Schutz. The location of this research is in Duri City of Gajah Sakti Village, Mandau Sub-district, Bengkalis Regency. Informants in this study amounted to ten people and determined by purposive technique. Data collection techniques used in the form of observation, interview and documentation. In achieving the validity of the data in this study, the authors use extension of participation and triangulation.The results of this study indicate that the intercultural interactions that.occur between ethnic Batak and ethnic Minang show accommodative behavior in the form of Facework through facial negotiation in the form of verbal and nonverbal when interacting in ethnic batak ethnic and ethnic Minang. Intercultural communication of ethnic Batak and ethnic Minang also experience obstacles such as cultural barriers, parangliustik, different perceptions and different nonverbal habits. These barriers are resolved through conflict managemeKeywords : Intercultural communication, Interpersonal Communication, negotation theory